Occurrence of multiple respiratory viruses in wastewater in Queensland, Australia: Potential for community disease surveillance - Ahmed, Warish; Bivins, Aaron; Stephens, Mikayla; Metcalfe, Suzanne; Smith, Wendy J.M.; Sirikanchana, Kwanrawee; Kitajima, Masaaki; Simpson, Stuart L. (Science of The Total Environment, 2023)
The early warning and tracking of COVID-19 prevalence in the community provided by wastewater surveillance has highlighted its potential for much broader viral disease surveillance. In this proof-of-concept study, 46 wastewater samples from four wastewater treatment plants (WWTPs) in Queensland, Australia, were analyzed for the presence and abundance of 13 respiratory viruses, and the results were compared with reported clinical cases. The viruses were concentrated using the adsorption-extraction (AE) method, and extracted nucleic acids were analyzed using qPCR and RT-qPCR. Among the viruses tested, bocavirus (BoV), parechovirus (PeV), rhinovirus A (RhV A) and rhinovirus B (RhV B) were detected in all wastewater samples. All the tested viruses except influenza B virus (IBV) were detected in wastewater sample from at least one WWTP. BoV was detected with the greatest concentration (4.96–7.22 log10 GC/L), followed by Epstein-Barr virus (EBV) (4.08–6.46 log10 GC/L), RhV A (3.95–5.63 log10 GC/L), RhV B (3.74–5.61 log10 GC/L), and PeV (3.17–5.32 log10 GC/L). Influenza viruses and respiratory syncytial virus (RSV) are notifiable conditions in Queensland, allowing the gene copy (GC) concentrations to be compared with reported clinical cases. Significant correlations (ρ = 0.60, p < 0.01 for IAV and ρ = 0.53, p < 0.01 for RSV) were observed when pooled wastewater influenza A virus (IAV) and RSV log10 GC/L concentrations were compared to log10 clinical cases among the four WWTP catchments. The positive predictive value for the presence of IAV and RSV in wastewater was 97 % for both IAV and RSV clinical cases within the four WWTP catchments. The overall accuracy of wastewater analysis for predicting clinical cases of IAV and RSV was 97 and 90 %, respectively. This paper lends credibility to the application of wastewater surveillance to monitor respiratory viruses of various genomic characteristics, with potential uses for increased surveillance capabilities and as a tool in understanding the dynamics of disease circulation in the communities. [Display omitted] •13 respiratory viruses were detected in four WWTPs in Queensland, Australia.•BoV, PeV, RhV A and RhV B were detected in all wastewater samples.•Wastewater IAV and RSV GC concentrations correlated with clinical cases.•12–17 days lead times were observed for IAV and RSV in wastewater samples.•The PPV for the presence of IAV and RSV in wastewater was 97 % for clinical cases.